2022
DOI: 10.3389/fonc.2022.835290
|View full text |Cite
|
Sign up to set email alerts
|

Glycerophosphoinositol Promotes Apoptosis of Chronic Lymphocytic Leukemia Cells by Enhancing Bax Expression and Activation

Abstract: An imbalance in the expression of pro- and anti-apoptotic members of the Bcl-2 family of apoptosis-regulating proteins is one of the main biological features of CLL, highlighting these proteins as therapeutic targets for treatment of this malignancy. Indeed, the Bcl-2 inhibitor Venetoclax is currently used for both first-line treatment and treatment of relapsed or refractory CLL. An alternative avenue is the transcriptional modulation of Bcl-2 family members to tilt their balance towards apoptosis. Glycerophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…A key class of regulatory molecules in the mitochondria‐associated apoptosis pathways is the Bcl‐2 family which targets mitochondria to regulate the intrinsic apoptosis pathways (Aouacheria et al., 2017). Bcl‐2 and Bax are the main anti‐apoptotic and pro‐apoptotic members of the Bcl‐2 family (Boncompagni et al., 2022). In our study, we found that after AA treatment, protein expression of Bax was increased and Bcl‐2 protein expression was decreased in RA‐FLS, resulting in a higher ratio of pro‐apoptotic and anti‐apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A key class of regulatory molecules in the mitochondria‐associated apoptosis pathways is the Bcl‐2 family which targets mitochondria to regulate the intrinsic apoptosis pathways (Aouacheria et al., 2017). Bcl‐2 and Bax are the main anti‐apoptotic and pro‐apoptotic members of the Bcl‐2 family (Boncompagni et al., 2022). In our study, we found that after AA treatment, protein expression of Bax was increased and Bcl‐2 protein expression was decreased in RA‐FLS, resulting in a higher ratio of pro‐apoptotic and anti‐apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%